(untitled) (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2025)
Background. Indopolycarbocyanine dyes are promising analytical reagents widely used in molecular spectroscopy. They are characterized by high molar extinction coefficients, which increase with the extension of the polymethine chain, and high quantum yields. The redox properties of these dyes have attracted significant attention. Upon interaction with oxidizing agents, their spectrophotometric and luminescent properties change markedly, enabling the development of new redox-based methods for detecting various analytes. Bromate ion is among the oxidants that requires strict control at the microquantities level. The aim of this work was to develop a sensitive spectrophotometric method for determining bromate in water using indopolycarbocyanine dyes as an analytical reagent. Methods. Spectrophotometric and potentiometric methods were used in the investigation. Results. The spectrophotometric characteristics of indopolycarbocyanine dyes, differing in the length of the methine chain, in the presence of sodium bromate were investigated. A decrease in the optical density of the dye solutions was observed upon interaction with bromate. The most noticeable change in optical density was observed for the indodicarbocyanine homologue. (Cy2). The optimal pH of the interaction was 1.5-2.0. The presence of coreagent potassium bromide enhanced the rate and intensity of decolorization of Cy2 by sodium bromate. The optimal reaction time was 20 min. Heating of the solution to 70oC for 20 min helps to improve of the reproducibility of the results. A spectrophotometric method for the quantitative determination of bromate was developed using an indodicarbocyanine dye containing three methine groups. Conclusions. Indopolycarbocyanine dyes are promising analytical reagents for the spectrophotometric determination of bromate. In the presence of bromate, the optical density of the dye solution decreases, serving as the analytical signal of bromate. The most intensive oxidation of the dye by bromate occurs in the presence of KBr (the optimal molar ratio of bromate : bromide is not lower than 1:50) in the pH range = 1.5-2.0 with heating of the reaction mixture to 700C for 20 min. The decreasing of the optical density of the dye solution in the presence of a mixture of bromate and bromide occurs most intensively for the indodicarbocyanine dye. A method for the spectrophotometric determination of bromate with the dye Су2 in the presence of co-reagent bromide has been developed. The linearity of the calibration graph is observed within the range of bromate ion concentrations of 0.02-1.0 mM, the limit of detection (LOD) and the limit of quantification (LOQ) are 0.01 and 0.038 mM (1,3 and 5,0 mg/l), respectively.